Increasing the yield of iron-dextran nanoparticles by ultrasonic treatment - Yang, Xianyu; Xin Gao (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
Iron-dextran nanoparticles are very useful for separating ciliate conjugating pairs. However, due to the low yield, their application is greatly limited. By ultrasonic treatment, their yield is greatly increased, which makes their application without any hesitation. This method will be introduced here.